Application of virtual simulation in clinical skills and operation courses - Wang, Li; Zhang, Feng; Xie, Hongxiang (Frontiers in Medicine, 2023)
Aim: This study investigated the effectiveness and prospect of applying virtual simulation operation（VSO）as a novel teaching tool in clinical skill and operation courses. Methods: A comparative test and survey study on the teaching effect of VSO was conducted with the clinical skill and operation course as the test course. The test group students received offline courses combined with online VSO practice. In contrast, the control group students received offline courses combined with instructional video review. The two groups were assessed using the Chinese medical school clinical medicine professional level test and a questionnaire survey. Results: The test group students scored significantly higher than the control group in the skills test (score difference: 3.43, 95% CI: 2.05-4.80) (p<0.001). Additionally, a significant increase in the percentage of high- and intermediate-score ranges and a decrease in the percentage of low-score ranges was observed (p<0.001). According to the questionnaire survey, 80.56% of the students were willing to continue using virtual simulation in their subsequent clinical skill and operation learning. Further, 85.19% of the students believed that the VSO is superior because it is unrestricted by time and space and can be performed anywhere and anytime compared to traditional operation training. Conclusion: VSO teaching can improve skills and examination performance. An entirely online operation that does not need special equipment can break through the spatiotemporal limitations of traditional skills courses. VSO teaching also suits the ongoing COVID-19 pandemic situation. Virtual simulation, a new teaching tool, has good application prospects.